Relationship development and construction supply chain management performance: The Malaysian scene - Zulhumadi, Faisal; Mohamed Udin, Zulkifli (2010)
As business operations expand in scope and borders, many successful companies of today are exploring new ways of gaining ground over their competitors in the market. These companies have to operate within the context of the environment that they are in, and in some countries, there are specific laws and situational factors that may influence how successful a company can operate. More to the point, this paper addresses some issues concerning the applicability of supply chain management in the context of the construction industry, with Malaysia being the backdrop to this research effort. More specifically, this paper will present the results of an initial effort in exploring the Construction Supply Chain Management (CSCM), focusing on the relationship development between the main players in the industry, namely the developer/client, contractor, and supplier.From the results of the study, it was revealed that there were several issues that have an effect on the success of the company which must be addressed, namely the issues of trust, information flow, and collaboration. A discussion based on these findings, which was obtained through a mix of qualitative and quantitative approaches, is also presented. Finally, this paper rounds of the research with a conclusion and some recommendations for future endeavours.